2017
DOI: 10.1080/01441647.2017.1314391
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to bicycle–motorised vehicle collisions: a systematic literature review

Abstract: Without prejudice to other rights expressly allowed by the copyright holders, this publication can be read, saved and printed for research, teaching and private study. Any other noncommercial and commercial uses are forbidden without the written permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 98 publications
(198 reference statements)
2
49
0
Order By: Relevance
“…Second, due to the time cost and financial and human consumption, the infrastructure characteristics were not collected in this study. As pointed out by a systematic review [20], the most important factor related to bicyclemotorized vehicle collisions was infrastructure characteristics. As e-bikes and bicycles share some similar features, these characteristics maybe also contribute to e-bike collisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, due to the time cost and financial and human consumption, the infrastructure characteristics were not collected in this study. As pointed out by a systematic review [20], the most important factor related to bicyclemotorized vehicle collisions was infrastructure characteristics. As e-bikes and bicycles share some similar features, these characteristics maybe also contribute to e-bike collisions.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that most e-bikers who were involved in collisions were middle-aged and male. Although there are several systematic reviews on factors contributing to bicycle collisions [19][20][21], few research was focused on contributing factors to e-bikes collisions. The only study was conducted by Hu et al [22] who found that age, road user 2 Journal of Advanced Transportation category, traffic rule violations, crash mode, impact type, and vehicle type were related to the severity of e-bike injuries.…”
Section: Introductionmentioning
confidence: 99%
“…The popular research trend today involves exploring the safety of bicycle (and at the same time PMV) routes [43][44][45]. Many researchers have put efforts into establishing methods to explicitly address bicycle safety by reflecting urban conditions, and have found that many factors influence safety, including the traffic volume, lane width, population density, highway classification, presence of vertical grades, one-way streets, and truck routes [21].…”
Section: Pmvs and Road Safetymentioning
confidence: 99%
“…However, cyclists are considered minority road users for several reasons and cycling is linked to safety concerns (Heinen, van Wee, & Maat, 2010;Schepers, Hagenzieker, Methorst, van Wee, & Wegman, 2014). To this end, safety considerations contribute to raising barriers to cycling and its promotion (Jacobsen & Rutter, 2012) and researchers have begun to focus their attention on cyclists' accidents and their contributory factors (Prati et al, 2018). Research suggests that men and women differ in terms of risky behaviour and involvement in accidents, including road crashes (Al-Balbissi, 2003;Cordellieri et al, 2016;Factor, Mahalel, & Yair, 2008;Massie, Campbell, & Williams, 1995;Pulido et al, 2016;Rhodes & Pivik, 2011;Santamariña-Rubio, P erez, Olabarria, & Novoa, 2014;Tom & Granie, 2011;Williams & Shabanova, 2003).…”
Section: Introductionmentioning
confidence: 99%